FGFR1 Antibody Validation and Characterization of FGFR1 Protein Expression in ER+ Breast Cancer. Issue 9 (12th October 2022) - Gonzalez-Ericsson, Paula I.; Servetto, Alberto; Formisano, Luigi; Sánchez, Violeta; Mayer, Ingrid A.; Arteaga, Carlos L.; Sanders, Melinda E.
Abstract : Clinical trials in patients with ER+ breast cancer with or without FGFR pathway somatic alterations have shown limited clinical benefit from treatment with FGFR tyrosine kinase inhibitors alone or in combination with endocrine therapy. This is likely because of an inadequate predictive biomarker to select appropriate patients. In this study, we evaluated 4 anti-FGFR1 antibodies in breast cancer cell lines and patient-derived xenografts with FGFR1 amplification. We correlated D8E4 expression in 209 tumors from postmenopausal patients with stage I-III operable ER+ breast cancer with FGFR1 amplification status as determined by fluorescence in situ hybridization. FGFR1 amplification was identified in 10% of tumors (21/209), 80% of which exhibited membranous FGFR1 expression; however, only 50% of amplified cases showed strong, complete membranous staining (3+) based on established criteria to score HER2 by immunohistochemistry. These findings suggest the combined evaluation of FGFR1 status by immunohistochemistry and fluorescence in situ hybridization may need to be incorporated into the selection of patients for trials with FGFR inhibitors.